A new indwelling urethral catheter (amSafeX) to verify the position of its balloon within the bladder during inflation - Anil Mandhani; Sunil Singh; Jakesh Reddy; Shrey Jain; Ramniwas Yadav (Urology Video Journal)
Introduction: Inserting a Foley catheter for urethral catheterization can lead to numerous iatrogenic injuries in patients, as it is difficult to ensure that the balloon is in the bladder during inflation. This video demonstrates the safety and effectiveness of a new design of indwelling urethral catheter (amSafeX) that confirms the presence of the balloon in the bladder during inflation. Design, setting, and participants: One hundred male patients who required a catheter for various reasons and 25 female postoperative patients were included in a prospective non-randomized interventional study. They were catheterized using the amSafeX catheter by a nurse or trainee doctor. The catheter features two draining eyes, with an additional eye proximal to the balloon and the usual distal eye blocked with an internal obturator attached to the string coming out of the drainage port. Standard instructions were given to follow the iSIP protocol of urethral catheterization. Data were collected and analyzed for the safety and efficacy of catheterization. Result: From Jan 2022 to Oct 2022, none of the 125 patients had any adverse events during catheterization, and the obturator could be removed easily in all procedures. There were no incidents of peri‑catheter leakage or urethral injury recorded during catheterization. The median duration of catheterization was 5 (3–12) days. Conclusion: The innovative design of amSafeX indwelling urethral catheter ensured that the bulb was always present in the bladder during inflation. This may eliminate the risk of urethral injury.